PENGARUH FAKTOR INTERNAL DAN AUDITOR EKSTERNAL TERHADAP MANAJEMEN LABA - Sulistyowati, 09.05.52.0146; Dwi Nugroho, Arief Himmawan (Students Journal of Accounting and Banking, 2013)
This study aims to examine the factors that influence earnings management. The importance of earnings information for both internal and external, prompting the management to make modifications earnings information in order to achieve their own goals. The factors discussed in this study is internal factors which consists of ownership, corporate governance, and the analysis offinancial statements and the external auditors. Earnings management is proxied by discretionary accruals are estimated using the model of Jones. The population in this study is a manufacturing company registered in Indonesia Stock Exchange (BEI) in 2008- 2011. Based on purposive sampling method, the number of samples in this study of 20 companies and the number of observations by 80 observational studies. Testing this hypothesis using multiple regression analysis. The results of this study indicate that institutional ownership, managerial ownership, audit committees, independent commissioners, the activity of the audit committee, and external auditors have a negative and significant effect on earnings management. Leverage variable has a negative and significant effect on earnings management. Profitability variable has a positive and significant impact on earnings management. Firm size has a positive and significant effect on earnings management.Keywords: earnings management, institutional ownership, managerial ownership, the audit committee, independent commissioners, the activities of the audit committee, the external auditor, leverage, profitability, firm size.